2016
DOI: 10.1186/s12885-016-2096-5
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association between polymorphisms in the CYP1A2 gene and risk of cancer: evidence from meta-analyses

Abstract: BackgroundPolymorphisms in the CYP1A2 genes have the potential to affect the individual capacity to convert pre-carcinogens into carcinogens. With these comprehensive meta-analyses, we aimed to provide a quantitative assessment of the association between the published genetic association studies on CYP1A2 single nucleotide polymorphisms (SNPs) and the risk of cancer.MethodsWe searched MEDLINE, ISI Web of Science and SCOPUS bibliographic online databases and databases of genome-wide association studies (GWAS). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 91 publications
(161 reference statements)
1
11
0
Order By: Relevance
“…CYP1A subfamily contains only two functional isoforms as CYP1A1 and CY-P1A2, and it has been addressed that CYP1A2 is expressed mainly in the liver; whereas the expression of CYP1A1 is mainly distributed outside the liver and involves the metabolism for aromatic hydrocarbon, CYP1A2 is expressed in the liver and metabolizes the aromatic amines and heterocyclic compounds (Wijnen et al, 2007;Lee et al, 2012;Lu et al, 2020). However, in recent days, the expression of CYP1A2 is identified in the pancreas and lung as well (Vukovic et al, 2016). Likewise, the detection of CYP1A2 expression in other tissues has been investigating to understand its function at each organ.…”
mentioning
confidence: 99%
“…CYP1A subfamily contains only two functional isoforms as CYP1A1 and CY-P1A2, and it has been addressed that CYP1A2 is expressed mainly in the liver; whereas the expression of CYP1A1 is mainly distributed outside the liver and involves the metabolism for aromatic hydrocarbon, CYP1A2 is expressed in the liver and metabolizes the aromatic amines and heterocyclic compounds (Wijnen et al, 2007;Lee et al, 2012;Lu et al, 2020). However, in recent days, the expression of CYP1A2 is identified in the pancreas and lung as well (Vukovic et al, 2016). Likewise, the detection of CYP1A2 expression in other tissues has been investigating to understand its function at each organ.…”
mentioning
confidence: 99%
“…However, our study could not nd any association of CYP2C9 genetic polymorphisms with OSCC. There are a large number of studies that have reported a similar lack of association of various CYP genetic variants with OSCC, as reviewed by Vukovic and colleagues (25) and Qiu and colleagues in excellent meta-analyses (26). However, this was the rst study attempting to nd out the association of CYP2C9 genetic polymorphisms with OSCC.…”
Section: Discussionmentioning
confidence: 97%
“…The studies of CYP1A2 expression are mainly focused on the liver to understand its role with respect to biotransformation and metabolism of exogenous substances and endogenous hormones (Mikhailova et al, 2006;Sugiyama et al, 2019). In the recent days, CYP1A2 expression in the other tissues including the pancreas, lung and ovary has been investigated (Vukovic et al, 2016;Hwang et al, 2020). Especially, there have been several articles identified that the expression of CYP family in the ovary is affected by several internal or external factors.…”
Section: Discussionmentioning
confidence: 99%
“…It has been known that CYP1A2 is mainly expressed in the liver to metabolize the aromatic amines and heterocyclic compounds of exogenous substances and endogenous hormones (Mikhailova et al, 2006;Sugiyama et al, 2019;Lu et al, 2020). However, in the recent days, it has been verified that CYP1A2 is also expressed in various organs in terms of the pancreas, lung and ovary (Hong et al, 2004;Vukovic et al, 2016;Hwang et al, 2020). Especially, it is found that expression of CYP isoforms in the ovary can be altered under 3-methylcholanthrene (3MC; Ah receptor ligand) treatment, the onset of puberty, methoxychlor (MXC; estrogenic endocrine disruptor) application (Dey et al, 1999;Symonds et al, 2006;Hwang et al, 2020).…”
mentioning
confidence: 99%